Crew Availability Ratio in Indonesian-Flagged Vessels: A Discrete Model Analysis of Sign-On–Sign-Off Cycle Effects on Sustainable Ship Operations - ., Moejiono; Santosa, Agus Dwi; Hartanti, Lusia Permata Sari; Putri, Indah Ayu Johanda; Amrullah, Romanda Annas (Journal of Cultural Analysis and Social Change, 2026)
This study analyzes the influence of the sign-on–sign-off (SoSo) cycle on sustainable operational continuity of Indonesian-flagged vessels using the Discrete Crew Availability Ratio Model. Grounded in IMO Resolution A.1047(27), SOLAS 1974, MLC 2006, and Indonesia's Ministerial Regulation PM No. 26 of 2022, the research applies a quantitative approach to 26,757 active Indonesian-flagged merchant vessels identified via Vessel Finder (AIS). Vessels are stratified into five gross tonnage (GT) categories—GT >10,000; GT 3,000–10,000; GT 1,500–3,000; GT 500–1,500; and GT <500—and classified as cargo or passenger ships. The discrete model computes crew group allocation using duty-cycle ratios and ceiling functions, incorporating attrition modeling through probabilistic outflow estimation. Under the baseline cycle of T=10 months on board and L=1 month leave, results indicate a total crew requirement of 327,120 seafarers, of whom 297,299 (90.9%) are on board and 29,821 (9.1%) are on leave. Attrition modeling at a rate of 0.30%/month yields an additional buffer demand of approximately 2,899 seafarers/year, increasing total requirements to 330,019 persons. Sensitivity analysis across 14 cycle scenarios (T=6 to T=12; L=1 to L=2) reveals the T10/L1 cycle as the optimal sustainable balance point across three Triple Bottom Line (TBL) dimensions: economic efficiency, seafarer social welfare, and environmental safety compliance. The study delivers evidence-based policy recommendations for regulators, shipping companies, and maritime education institutions aligned with SDGs 8, 9, and 14.